Engaging health sciences librarians on data ethics: case study on a pilot curriculum - Nicole Contaxis; Fred WZ LaPolla; Genevieve Milliken (Journal of the Medical Library Association, 2023)
Background: Ethical decision-making regarding data collection, visualization and communication is of growing importance to librarians, with special relevance to those in medical and data fields. Data ethics training opportunities for librarians, however, are uncommon. To fill this gap, librarians at an academic medical center developed a pilot data ethics curriculum for librarians across the U.S. and Canada.